Topological aspects of dynamic systems - Sharko , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We give a definition of a minimal vector field whose singular elements are all hyperbolic. For a particular class of smooth manifolds we compute the number of minimal Morse-Smale vector fields. We find necessary and sufficient conditions for the L-equivalence of Morse-Smale vector fields. For Kupka-Smale fields we introduce a Lyapunov 1-form which we use to write down inequalities for the singular elements.